Research Priorities in the field of Anaemia in India - Sinha, Anju; Kulkarni, Bharati; Mithra, Prasanna; Mahajan, Preetam; Upadhyay, Ravi; Nair, Sree kumar; Sharma, R. S. (Indian Journal of Community Health, 2018)
Anaemia is a health problem that caused most disability in India over a decade (2005-2016) according to the Global Burden of Disease study(1). India has the maximum number of anaemic women and children in the world(2). As per the recent National Family Health Survey-4 (2015-16), about 58% children (6-59 months), 53% women (15-49 y) and 23% men were suffering from various degrees of anaemia(3). Aanaemia affects the general health of the total population taking toll for high mortality as well as morbidity and attenuating the optimal expression of the potentials of both physical and mental capacity of our population. Improving nutritional status of the vulnerable sections of the population and reducing anaemia is of paramount importance for improving health and the human capital development in the country(4).